1999
DOI: 10.1016/s0009-9236(99)70078-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-genotype correlation of in vitro SN-38 (active metabolite of irinotecan) and bilirubin glucuronidation in human liver tissue with UGT1A1 promoter polymorphism

Abstract: The results indicate a significant association of UGT1A1 phenotype and genotype based on in vitro phenotypic measurements. The clinical significance of our finding remains to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
205
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(225 citation statements)
references
References 37 publications
14
205
0
3
Order By: Relevance
“…14,15 A significant correlation between SN-38 and bilirubin glucuronidation has been found, high serum T-Bil concentration seemed to be a reasonably good predictor of lower irinotecan clean rate. [16][17][18] In the present study, the (TA)7 allele was significantly associated with higher T-Bil concentrations, in line with previous reports. 15,19 However, different to Koreans, no association between 211A allele and bilirubin level was found.…”
Section: Intra-ethnic Differences In Genetic Variantssupporting
confidence: 93%
“…14,15 A significant correlation between SN-38 and bilirubin glucuronidation has been found, high serum T-Bil concentration seemed to be a reasonably good predictor of lower irinotecan clean rate. [16][17][18] In the present study, the (TA)7 allele was significantly associated with higher T-Bil concentrations, in line with previous reports. 15,19 However, different to Koreans, no association between 211A allele and bilirubin level was found.…”
Section: Intra-ethnic Differences In Genetic Variantssupporting
confidence: 93%
“…122 Irinotecan {CTP-11 or 7-ethyl-10-[4-(1-piperidino)-1-piperidino] carbonyloxy camptothecin} is an anticancer drug clinically used in combination with 5-fluorouracil and leucovorin as the first-line treatment of metastatic colorectal cancer. CPT-11 is biotransformed by carboxylesterases into a pharmacologically active metabolite, SN-38 (7-ethyl-10-hydroxycamptothecin), 123 which is responsible for severe toxicity.…”
Section: Ugt1a1mentioning
confidence: 99%
“…This hypothesis is supported by the observation of an inverse relation between SN-38 glucuronidation and the severity of diarrheas occurring in patients treated with irinotecan. 122,124 In a prospective study comprising irinotecan-treated cancer patients, the group of Iyer et al 61 observed that UGT1A1 promoter activity influences the extent of SN-38-G formation and is associated with the incidence of adverse reactions, mostly neutropenia and diarrhea. A retrospective clinical study of Japanese cancer patients revealed an association between genetic Pharmacogenomics of human UGT enzymes C Guillemette In the case of rare hyperbilirubinemia, as in CN type I, the UGT1A1*28 variant promoter does not seem to play a significant role, while in the case of CN type II, the presence of the *28 allele was shown to affect the clinical characteristics of the disease.…”
Section: Ugt1a1mentioning
confidence: 99%
“…[13][14][15] While the primary selective pressure for UGT1A enzyme function may have been metabolism of endogenous molecules, UGT1A function is necessary for elimination of exogenous compounds such as the anti-cancer drug irinotecan. [16][17][18] The same common UGT1A1 variants associated with mild elevations of serum bilirubin are associated with diminished in vitro glucuronidation of the active irinotecan metabolite, SN-38, [19][20][21][22] and prolonged exposure and increased toxicity in patients receiving this agent. [23][24][25] As shown by Sai et al, 25 re-sequencing of the UGT1A1 gene in 85 Japanese patients treated with irinotecan confirmed that the haplotypes containing lower expression variants were associated with both a low SN-38G/SN-38 AUC ratio and elevated pretreatment bilirubin concentration.…”
Section: Introductionmentioning
confidence: 99%